Future Increase in Aridity Drives Abrupt Biodiversity Loss Among Terrestrial Vertebrate Species. Issue 4 (3rd April 2023) - Liu, Xiaoping; Guo, Renyun; Xu, Xiaocong; Shi, Qian; Li, Xia; Yu, Haipeng; Ren, Yu; Huang, Jianping
Abstract: The planet is predicted to become drier because of accelerating global warming, increasing great challenges to the survival of terrestrial species. However, the understanding of when and where increasing aridity in the future will lead to abrupt biodiversity loss is still limited. Here, we predicted the spatiotemporal dynamics of future vertebrate biodiversity loss driven by increasing aridity at the assemblage scale under the scenario framework of the shared socio‐economic pathways (SSPs) and representative concentration pathways (RCPs). The results show that, under the high‐emissions scenario of SSP5‐8.5, more than 24.19% of terrestrial assemblages are projected to have at least one vertebrate species exposed to unprecedented aridity conditions by 2100, leading to 55.29% of terrestrial vertebrate species experiencing local habitat loss. In addition, the mean magnitude of global exposure is expected to reach 17.47% by 2100. Within these assemblages, most species will be simultaneously exposed to unprecedented aridity conditions, with an average exposure abruptness of 78.00%, most of which will occur intensively after 2050. If we manage to reduce greenhouse gas emissions to the SSP1‐2.6 (SSP2‐4.5) scenario, the magnitude of exposure can significantly decrease to 7.35% (10.56%), and the onset of exposure can be delayed by 43 (30) years, averaging approximately 30% (14%) of vertebrate species from local habitat loss. Our findings also highlight that the concurrent extremes of increasing aridity and rising temperature in Southeast Asia and Amazon rainforests may amplify exposure risks, which can motivate decision‐makers to respond early and eﬀectively to mitigate abrupt ecological disruption. Plain Language Summary: The global land surface is predicted to become more drier in the future due to the accelerating global warming, which places great challenges on the survival of terrestrial species. In this paper, we predicted the future spatiotemporal dynamics of biodiversity loss of vertebrate species as a result of the increase in aridity, trying to understand when and where the increasing aridity will cause biodiversity loss intensively and lead to abrupt ecological disruption. We found that, under the high‐emissions scenario (∼4.4°C global temperature rise), more than 24.19% of global terrestrial assemblages are projected to have at least one vertebrate species exposed to aridity condition exceeding their niche, leading to the consequence that 55.29% of species will experience habitat loss. The exposure events within most terrestrial assemblages will occur simultaneously after 2050. If we manage to reduce emissions to the low (intermediate)‐emissions scenario (∼1.8°C and 2.7°C global temperature rise), the onset of exposure can be delay by 43 (30) years. Our findings also highlight that the concurrent extremes of increasing aridity and rising temperature in Southeast Asia and Amazon rainforests may amplify exposure risks, which can motivate decision‐makers to respond early to mitigate abrupt ecological disruption. Key Points: We predicted and highlighted the risk of abrupt biodiversity loss in terrestrial vertebrate species driven by increasing aridity More than 24% of terrestrial assemblages will be exposed to unprecedented aridity, and 55.29% of species will experience local habitat loss Concurrent extremes of increasing aridity and rising temperature in Southeast Asia and Amazon rainforests may amplify exposure risks